Analysis of the Impact of the 12% Value-Added Tax (VAT) Rate Increase on Consumer Behavior and Public Welfare in Indonesia - Nopi Tikasari (Journal of Research in Social Science and Humanities, 2025)
The implementation of the 12% VAT rate in 2025 has generated various public responses regarding its impact on prices, purchasing power, and household economic welfare. This study aims to analyze the influence of public understanding and perception of the policy, changes in consumption behavior, and economic welfare on public opinions and expectations regarding the 12% VAT policy. A quantitative survey method and regression analysis were employed to examine the relationship among the variables. The findings indicate that all research instruments are valid, reliable, and meet classical assumption requirements, making them suitable for further analysis. The results show that public understanding and perception, consumption behavior, and economic welfare significantly affect public opinions and expectations, with consumption behavior emerging as the strongest predictor. This suggests that price increases resulting from the VAT adjustment directly influence consumption patterns and shape public attitudes toward the policy. The study concludes that the 12% VAT policy not only contributes to state revenue but also generates notable economic and social implications that must be carefully managed. Therefore, it is recommended that the government enhance policy communication, strengthen tax literacy, provide targeted social protection programs, and ensure fiscal transparency to foster greater public acceptance of the policy.